2008
DOI: 10.1021/om800793q
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Dibenzazepine-Based P-Alkene Ligands and Their Rhodium Complexes: Catalytic Asymmetric 1,4 Additions to Enones

Abstract: N-Dichlorophosphanyldibenzo[b,f]azepine (6) reacted with (−)-2,3-O-isopropylidene-d-threitol, (R)-taddol, (R,R)-diethyltartrate, (R,R)-diethyltartrate, (S)-binaphthol, α,α-diphenyl-l-prolinol, and (S)-proline to form the corresponding chiral P-alkene ligands 7−12. These ligands were then used to synthesize dinuclear chloro-bridged Rh(I) complexes 13−18 with the general formula [Rh(μ-Cl)(P-alkene)]2. It was shown by X-ray diffraction analyses that these P-alkenes indeed act as bidentate ligands for Rh(I). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 35 publications
(31 reference statements)
3
43
0
2
Order By: Relevance
“…[241,242] Further studies with dibenzazepine-based phosphoramidites were conducted, although lower selectivity was found. [243] A related tandem conjugate addition/allylation reaction in aqueous media was also described. [244]…”
Section: General Considerationsmentioning
confidence: 99%
“…[241,242] Further studies with dibenzazepine-based phosphoramidites were conducted, although lower selectivity was found. [243] A related tandem conjugate addition/allylation reaction in aqueous media was also described. [244]…”
Section: General Considerationsmentioning
confidence: 99%
“…Mit Biphenol-Phosphoniten und Phosphoramiditen wurden ähnliche Ergebnisse erzielt, [241,242] dagegen führten Dibenzazepin-Phosphoramidite zu niedrigeren Selektivitäten. [243] Des Weiteren wurde eine ähnliche konjugierte Additions-/Allylierungsreaktion in wässrigem Medium beschrieben. [244] 44).…”
Section: Rhodiumkatalysierte Konjugierte Additionen Von Boronsäurenunclassified
“…The kinetic study of the Rh/L43 system in ECA, revealed that the catalytic activity with L43 to be intermediate to that of diphosphines and dienes [130]. Good activities and enantioselectivities were obtained with ligands L44 [131], amidophosphine-alkene L45 [132] (first synthesized by Carreira [133]) and with the chiral phosphine-olefin L46 [134].…”
Section: Mixed Donor Ligandsmentioning
confidence: 99%